2021
DOI: 10.1371/journal.pone.0259310
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of preterm neonatal mortality at Mbarara Regional Referral Hospital in South Western Uganda

Abstract: Introduction Preterm neonatal mortality contributes substantially to the high neonatal mortality globally. In Uganda, preterm neonatal mortality accounts for 31% of all neonatal deaths. Previous studies have shown variability in mortality rates by healthcare setting. Also, different predictors influence the risk of neonatal mortality in different populations. Understanding the predictors of preterm neonatal mortality in the low-resource setting where we conducted our study could guide the development of interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
4
14
0
Order By: Relevance
“…Likewise, similar findings were observed in Orotta Pediatric Hospital of Eritrea and New Haven Hospital United States. 53,56,57 Convergence of the findings could be because the lower their gestational age the weaker their body sustains the sequela of RDS.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, similar findings were observed in Orotta Pediatric Hospital of Eritrea and New Haven Hospital United States. 53,56,57 Convergence of the findings could be because the lower their gestational age the weaker their body sustains the sequela of RDS.…”
Section: Discussionmentioning
confidence: 98%
“…We also found that preterm neonates having a history of respiratory distress syndrome had a 1.81 times higher risk of death than those who do not have it, which is supported by studies in Uganda and Rwanda. 37,41 In addition, those having hyaline membrane disease had almost three times higher hazard of death compared to those who do not have it. It might be because the immaturity of the lung fails to produce a liquid called surfactant, which hinders the full expansion of the lungs and leads to a shortage of oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled incidence proportion of preterm mortality was 30%, which is higher than findings from India, Pakistan, England, and Uganda. [35][36][37] The discrepancy might be due to the difference in socio-economic status and infrastructure for caring the sick neonates. This finding is lower than the findings of a study conducted in the United States, 38 which might be due to the clinical condition difference, where preterm neonates in a study done in the United States had a comorbid congenital diaphragmatic hernia, which reduces survival probability and because the study design differs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The facility has a full-time operating theatre with a caesarean section rate of 40%. 19 The hospital offers specialized obstetric and gynecological operations, it also has an active pediatric ward with special care units for pre-matures and neonates. Mothers are referred to MRRH in search for specialized services which are lacking at the health centre IVs.…”
Section: Methodsmentioning
confidence: 99%